Domestic violence perpetrators: evidence-informed responses - Devaney, John (Routledge advances in social work, 2016)
Introduction -- Defining and measuring domestic violence -- Explanations for domestic violence -- Typologies of domestic violence perpetrators -- Changing perpetrator behaviour -- Evidence informed interventions -- Conclusions